A decision support system for evaluating information technology projects - Atlı, Şeyhmus. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The increasing pressures of global competition, the continuous stream of innovative technologies, and the introduction of new products to satisfy customer needs make Information Technology (IT) projects a key element of the business market. Due to the proactive nature of IT, its value is difficult to evaluate in advance, which means that organizations often select to implement IT projects that do not realize the intended benefits. A well-designed selection process for IT projects should decrease the failure rate of implemented solutions and increase the financial success of the companies. This study attempts to resolve the IT project selection problem in the companies by combining an ANP with fuzzy logic and strengthening the solution with a Monte Carlo simulation. While there have been previous attempts to combine any two of the three underlying methods, the combination of all three should lead to a method that gives optimal results for any given case. The study reviews existing literature on IT project selection. Every criteria that can be relevant to IT projects are obtained with literature review and currently significant ones are selected using feedback from experts. The most effective ones respectively finance, organizational goals, risk and technical are used for the study. Based on existing knowledge and analysis of problems facing the companies, a detailed theoretical model is developed and applied to a real-world case study. In this context, this study should be useful to IT project selection committee members and researchers in the field of decision making, but it should also be of interest to IT managers of companies.
Keywords: Information technology.; Decision support systems.